Investigation on the Marine Corrosion Behavior and Mechanism of Fe3O4 Film Using ReaxFF-MD - CHEN Xiangrui, CHEN Yang, WANG Bing, GU Bin (Cailiao Baohu)
In order to explore more deeply and comprehensively the intrinsic mechanisms of corrosion behavior of steel in the marine environment，the ReaxFF molecular dynamics (ReaxFF-MD) method was employed to study the marine corrosion behavior of Fe3O4 in steel passivation film under different NaCl contents，temperatures and strain conditions.By characterizing the surface corrosion morphology，testing the quality loss curve，number density curve，radial distribution function (RDF) curve and simulating the atomic structure evolution at the reaction interface，the process and differences of Fe3 O4 marine corrosion behavior under different conditions were analyzed，and the mechanisms of Fe3O4 marine corrosion and the influence of different factors were revealed at the atomic scale.Results showed that the marine corrosion of Fe3O4 went through three stages: the adsorption stage of water molecules on the surface of Fe3O4 substrate in marine environment，the rapid corrosion stage of substrate and the corrosion saturation stage.During the corrosion process，the increase in NaCl content in the marine environment promoted the adsorption of water molecules on the substrate surface，enhancing the interaction between substrate atoms and water molecules.Moreover，the increase in temperature would cause expansion deformation and enhance molecular motion，reducing the difficulty of bond breaking behavior of matrix atoms.External strain led to an increase in atomic bond lengths and a decrease in atomic coordination numbers within the Fe3O4 matrix，thereby exacerbating the corrosion process.Besides，when the external load was applied，the strain in the substrate increased with the progression of corrosion，and the defect concentration area was generated under high strain loading.